2018
DOI: 10.1111/tpj.14045
|View full text |Cite
|
Sign up to set email alerts
|

Starch degradation, abscisic acid and vesicular trafficking are important elements in callose priming by indole‐3‐carboxylic acid in response to Plectosphaerella cucumerina infection

Abstract: A fast callose accumulation has been shown to mediate defence priming in certain plant-pathogen interactions, but the events upstream of callose assembly following chemical priming are poorly understood, mainly because those steps comprise sugar transfer to the infection site. β-Amino butyric acid (BABA)-induced resistance in Arabidopsis against Plectosphaerella cucumerina is known to be mediated by callose priming. Indole-3-carboxylic acid (ICOOH, also known as I3CA) mediates BABA-induced resistance in Arabid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 62 publications
3
43
0
Order By: Relevance
“…Furthermore, BABA priming affects the methylome of plants, resulting in a transcriptional memory of the event which can affect following generations (Kuźnicki et al, ). Recent studies showed how BABA perception reshapes the primary metabolism of plant cells by boosting the TCA cycle and mobilizing starch reservoirs towards callose synthesis and deposition at the infection sites (Gamir et al, ; Pastor, Balmer, Gamir, Flors, & Mauch‐Mani, ; Yao, Zhong, Wang, Yan, & Wu, ).…”
Section: Interconnections Between Gaba and Other Stress‐related Aminomentioning
confidence: 99%
“…Furthermore, BABA priming affects the methylome of plants, resulting in a transcriptional memory of the event which can affect following generations (Kuźnicki et al, ). Recent studies showed how BABA perception reshapes the primary metabolism of plant cells by boosting the TCA cycle and mobilizing starch reservoirs towards callose synthesis and deposition at the infection sites (Gamir et al, ; Pastor, Balmer, Gamir, Flors, & Mauch‐Mani, ; Yao, Zhong, Wang, Yan, & Wu, ).…”
Section: Interconnections Between Gaba and Other Stress‐related Aminomentioning
confidence: 99%
“…Defense response induced by BABA was also observed in the expression of callose synthase genes. Callose accumulation was also reported in Plectosphaerella cucumerina infection, and significantly increased with indole‐3‐carboxylic acid priming …”
Section: Discussionmentioning
confidence: 53%
“…19,20,[22][23][24] Similar pathways will be stimulated by different priming stimuli/biotic stress. 57 In this study, both BABA and SBA induced the genes involved in the isoflavone phenylpropanoid pathway. Most genes were significantly induced with the combination of BABA and SBA treatment, which were consistent with the increase of isoflavone amount.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations